Object oriented system reliability measurement techniques: A Review - Kashyap, Shailja (IJRDO -Journal of Computer Science Engineering, 2016)
Reliability of a software system is a major factor to quantify the quality of a software system .In the competitive world of software industries one cannot compromise with the quality of the system, so the reliability .High reliable software product have been considered as the high quality product in the market. A lot of research work have been done in past decade to estimate the reliability of a software system .In this review paper, we present a systematic literature review on object oriented system reliability measurement techniques .In this paper, we aim to gather, study and present the various available reliability measurement techniques for object oriented software systems.